The Role of AUKUS in Australia’s Military Capacity Building Strategy - Lubis, Lia Aulia; Perwita, Anak Agung Banyu; Hadisancoko, Rizerius Eko (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper explores the role of AUKUS in enhancing Australia's military capacity amid evolving Indo-Pacific geopolitics. The AUKUS partnership between Australia, the UK, and the US aims to increase Australia's defense capabilities, focusing on nuclear-powered submarines, cyber security, AI, and underwater warfare. The analysis shows how AUKUS addresses Australia's military challenges by offering advanced technology and strategic support. The SSN-AUKUS submarines symbolize a major advancement in Australia's naval capabilities. The partnership also promises economic and social benefits, including job creation and infrastructure development. However, the study also notes potential drawbacks, such as increased regional tensions and the risk of an arms race, highlighting the need for balanced diplomatic effort.